Multicultural Awareness Scale for Junior High School Students: Adaptation, Reliability, and Validity - Hapsari, Novita Tri; Basuki, Agus (Bulletin of Counseling and Psychotherapy, 2025)
Multicultural awareness is important for students in the 21st century, and its level needs to be measured using standardized instruments. This study aimed to examine the acceptability of the multicultural awareness instrument developed by Ali (2011) for Junior High School (SMP) students in Sukoharjo, Indonesia. The instrument adaptation process involved five stages with a sample of 308 participants. Acceptability of the instrument was analyzed using the RASCH Model. The research findings present the instrument's ability to measure what is intended to measure, the relationship between respondents and items, and the difficulty level of the items. The results indicate that the multicultural awareness instrument is valid and reliable for application among students. Future researchers are suggested to examine this instrument at the senior high school level and use it as a measure of students' multicultural awareness for experimental research. Moreover, integrating multicultural awareness into the learning process can enhance educational practices.